Effect of Remittances on Economic Growth in Nepal (The Lumbini Journal of Business and Economics, 2021)
This study aims to explore the effect of Remittances on Economic growth of Nepal using Augmented Dickey Fuller Unit Test (ADF) to check the stationary of variables where Gross Domestic Product is dependent variable and Remittance, Investment, Consumption and Government Expenditure are independent variables. All the variables are in current price and data have been collected from Nepal Rastra Bank, Economic Survey and Ministry of finance, Government of Nepal spanning from 1989/90 to 2017/18. Simple regression equation estimated by ordinary least square (OLS) method. The other analytical tools like unit root test, heteroscedasticity test, normality test, serial correlation test, R-squared test, t- test, F-test D-W test, has been used. Empirical result finds that Investment and consumption are statistically significant and positive effect on economic Growth of Nepal. Remittances and Government expenditure are statistically insignificant and positive effect on GDP. Residuals are homoscedastic, free from serial correlation and normally distributed.